Identification of two distinct hereditary hemorrhagic telangiectasia patient subsets with different hepatic perfusion properties by combination of contrast-enhanced ultrasound (CEUS) with perfusion imaging quantification - Schelker, Roland C.; Andorfer, Kornelia; Putz, Franz; Herr, Wolfgang; Jung, Ernst-Michael (PLoS ONE, 2019)
Background Hereditary hemorrhagic telangiectasia (HHT) is marked by arteriovenous fusion comprising hepatic vascular malformations (HVaMs) with the chance of bleeding. Aims We investigated HVaMs in HHT patients by combination of contrast-enhanced ultrasound (CEUS) with perfusion imaging quantification to be able to sub-classify a high risk cohort of asymptomatic HHT patients. Methods The imaging characteristics on CEUS in 34 patients (aged 21-84 years; mean 58.9) with HHT were retrospectively evaluated. Real-time contrast harmonic imaging, sulfur hexafluoride-filled microbubbles and motion adjustment were utilized. Cine loops of the liver were digital stored, perfusion was quantified using a software reading DICOM data's. Results HVaMs were diagnosed in 31 out of 34 patients. Significant uppermost peak enhancement (PE), wash-in area under the curve (WiAUC) and wash-in perfusion index (WiPI) were identified in the shunt region (100%), next in the hilar region (PE 32.6%; WiAUC 33.9%; WiPI 34.1%), and the lowest in the hepatic parenchyma (PE 10.2%; WiAUC 12.0%; WiPI 9.5%). The perfusion parameters in the shunt region compared to the other regions were significantly increased in one subgroup of patients. Consistent with this, the intrahepatic portal vein diameter and Buscarini grading was significantly higher, while portal vein peak velocity was significantly lower in this patient subset. By statistical analysis, we could correlate PE and WiPI to these clinical parameters, while WiAUC showed no clinical association. Conclusions For the first time we combined CEUS findings with motion adjustment software to quantitative determine perfusion parameters of a cohort of HHT patients. Hereby, we could identify a subset of HHT patients with two markedly increased parameter values in the shunt region compared to the hilus/hepatic parenchyma. This could contribute to sub-classify a high-risk group of HHT patients with therapeutic indication.
CRIS-Team Scopus Importer:2023-03-23